Gestión de la energía eléctrica en la edificación de la Unidad Académica de Ciencias Agropecuarias y Recursos Naturales de la Universidad Técnica de Cotopaxi, ciudad de Latacunga durante el período 2012 - 2013. Diseño de un programa de eficiencia energética para dar soluciones técnicas y económicamente viable. - Moreano Martínez, Edwin Homero (2013)
The theme of conservation and efficient use of energy, the concept of energy efficiency is a resource that becomes effective as a result of global warming issues, generated as a result of environmental pollution greenhouse gases, whose object is part of developing solutions and implementation of measures to remedy and stop environmental degradation of the planet. In the present researching refers to investigations related to energy management. From a characterization of the Academic Unit of Agricultural Sciences and Natural Resources at the Technical University of Cotopaxi, it presents a few information in the management in relation to energy management. Consumption are analyzed carriers, key positions are declared. It evaluated the behavior of demand, and the main electrical variables. We present a possible solution to the problems of electrical infrastructure, from the standpoint of technical and economic. Requirements are proposed for efficient energy management in building the academic unit derived from the analysis of an energy assessment, and as a result of applying the Total Management Technology Energy Efficient.